EVALUATION OF PHYTO-EXTRACTION POTENTIALS AND PERFORMANCE OF FALSE SESAME (CERATOTHECA SESAMOIDES) UNDER INDUCED SOIL POLLUTION BY AUTOMOBILE LUBRICANT IN SAVANNA ECOREGION - Babajide; Popoola; Gbadamosi; Oyedele; Liasu (International Journal of Research -GRANTHAALAYAH, 2017)
While strategizing towards achieving improved soil fertility for sustainable tropical crop production, timely application of fertilizers on regular basis alone is not the University of Technology, Ogbomoso, Oyo State, Nigeria best approach, particularly on polluted soils. However, seeking for reliable natural, biological and environment friendly means of ensuring effective riddance of toxic elements or heavy metals from tropical agricultural soils is equally a worthwhile technology. An open-field potted experiment was conducted during early raining season of 2016 (March-July), at the Teaching and Research Farms of Oyo State College of Agriculture and Technology, Igboora, to investigate the effect of spent engine oil polluted soil conditions on performance and heavy metal accumulation potentials of Ceratothecasesamoides. Spent engine oil was applied at different concentrations (0.0ml, 50.0ml, 100.0ml, 150.0ml, and 200.0ml to each pot containing 7kg soil. Four pots per treatments were used. The trial was arranged in Completely Randomised Design (CRD), replicated three (3) times. Data were collected on growth parameters (number of leaves, plant height, stem girth, leaf length and leaf breadth). The data were subjected to analysis of variance (ANOVA) and Duncan Multiple Range Test (DMRT) was used to the means. Pre and post-cropping soil analyses were carried out, for determination of nutrient concentrations. Also, after the termination of the experiment, plant samples were collected from each of the pots for oven-drying followed by determination of nutrient concentrations (including the heavy metals). Oil pollution significantly affected growth and heavy metal accumulation of the test-crop. Growth decreases with increasing rate of lubricant application, while the heavy metal concentrations in the test-crop increased with increasing concentrations of the applied spent engine oil. Thus, Ceratothecasesamoides is a wild plant which could be easily exploited for its heavy metals hyper-accumulative or phyto-extractive potentials, so as to reclaim heavy metals polluted soils from toxicity, for sustainable crop production.